Toxicity, bioaccumulation and mitigating strategies of heavy metals stress on morpho-physiology of spinach - Bibi, Ayesha; Rasul, Fahd; Shahzad, Sobia; Sakrabani, Ruben; Din, Wasi ud; McKenna, Patrick; Sajid, Muhammad (Springer, 2024)
The purpose of this review was to look into the different ways that heavy metal stress affects spinach, and how hazardous they are to soil, people's health, and plant ecosystems. Heavy metals in soil are caused by anthropogenic and industrial activity, and when they accumulate in food chains, they pose a major risk to human health. This paper presents an overview of heavy metals' negative impacts on soil fertility, plant physiology, and human health. Using spinach as a model plant, it is simple to cultivate and maintain, making it a diverse choice for studying how plants respond to stresses such as heavy metals. They describe how heavy metal stress affects spinach morphology and physiology, including absorption, detoxification, and translocation throughout the plant system. Understanding these procedures is critical when assessing the potential risks associated with the accumulation of hazardous components in spinach's edible parts. This review investigates the impact of heavy metal stress on the nutritional quality and yield of spinach after metal exposure. It is critical to investigate numerous strategies for reducing heavy metal stress in spinach, including soil remediation approaches, phytoremediation capabilities, and genetic procedures aimed to increase plant resistance to metals. The goal of this overview is to shed light on the mechanisms underlying the effects of heavy metals on spinach and to propose strategies to alleviate them, thereby protecting agricultural sustainability and public health (Fig. 1).
Keywords: 41 Environmental Sciences; 4105 Pollution and Contamination; Generic health relevance; 2 Zero Hunger; Heavy metals stress; MB (metal binding detoxification) detoxification; Mitigation strategies; Phytoremediation; Soil amendment; Micronutrients; Spinach